A new species of Microcaecilia Taylor, 1968 (Amphibia: Gymnophiona: Siphonopidae) from Amazonian Brazil - Wilkinson, Mark; Antoniazzi, Marta Maria; Jared, Carlos (Zootaxa, 2015)
A new species of siphonopid caecilian, Microcaecilia butantan sp. nov., is described based on four specimens from Belterra, in the State of Pará, Brazil. The new species differs from all other Microcaecilia in having a combination of more than 135 primary annuli and long premaxillary-maxillary tooth series that extend posteriorly beyond the choanae. Some specimens were dug from soil in a cupuaçu (Theobroma grandiflorum) plantation suggesting that this form of agriculture provides an environment suitable for at least some caecilians.